Response to a standard behavioral weight loss intervention by age of onset of obesity. (25th July 2016) - Rupp, K.; Taverno Ross, S. E.; Lang, W.; Jakicic, J. M.
Summary: Background: The purpose of this study was to examine weight loss, physical activity, fitness and diet changes in response to a standard behavioral weight loss intervention in adults with self‐reported juvenile onset ( n  = 61) or adult onset ( n  = 116) obesity. Methods: Participants ( n  = 177; 43.0 ± 8.6 years; body mass index [BMI] = 33.0 ± 3.4 kg m −2 ) engaged in an 18‐month standard behavioral weight loss intervention. Participants were randomized into three different intervention groups as part of the larger parent trial. BMI, physical activity, fitness and diet were assessed at baseline, 6, 12 and 18 months. Separate adjusted mixed models were constructed using SAS version 9.4 (SAS Institute, Cary, NC). Results: There was significant weight loss, increased physical activity, improved fitness and reduced caloric intake over time ( p  < 0.001). There were no significant differences in these outcome variables by obesity onset group. However, there was a significant group by time interaction for fitness ( p  = 0.001), with the adult onset making significantly greater gains in fitness from baseline to 6 months ( p  < 0.001); however, this difference was no longer present at 12 or 18 months. Conclusions: With the exception of fitness at 6 months, weight loss, physical activity and diet did not differ between juvenile onset and adult onset participants, suggesting that those with juvenile onset obesity are equally responsive to a standard behavioral weight loss intervention in adulthood.